Association of atrial myopathy in mitral valve disease on safety outcomes in left atrial appendage closure: original paper - Kany, Shinwan Salah; Skibowski, Johanna; Müller, Claus-Heinrich; Geist, Volker; Schmitt, Jörn; Niroomand, Feraydoon; Hailer, Birgit; Pleger, Sven Torsten; Akın, Ibrahim; Hochadel, Matthias; Senges, Jochen; Lubos, Edith (Clinical research in cardiology, 2023)
Patients undergoing left atrial appendage (LAA) occlusion (LAAO) are multi-morbid, including mitral valve disease (MVD) which is associated with anatomic changes of the left atrium (LA). This study aims to identify how atrial myopathy in MVD influences outcomes in LAAO.